2012
DOI: 10.4161/auto.21830
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3 induces FOXO1-dependent autophagy by activating the AKT1 signaling pathway

Abstract: Abbreviations: ATG, autophagy related; FOXO1, forkhead box O1; FOXO3, forkhead box O3; GFP, green fluorescent protein; MAP1LC3, microtubule-associated protein 1 light chain 3; PIK3CA, class I PI3K catalytic subunit the BECN1-PtdIns3K complex to promote autophagosome formation. 16,17 Recent evidence has revealed that the FOXO protein family members FOXO1 and FOXO3 promote autophagy. [18][19][20][21][22][23] In skeletal muscle cells, FOXO3 directly upregulates autophagy-related genes, such as microtubule-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 68 publications
(106 reference statements)
11
109
0
Order By: Relevance
“…Our findings provide evidence for a CTLA4-mediated transcriptional-dependent regulation of autophagy in DCs though activation of the PI3K/Akt axis that results in nuclear exclusion of FoxO1 and decreased transcription of Lc3b. Nuclear presence of FoxO1 is a prerequisite for transcriptional activation of autophagy genes in a process that is controlled by Akt (55). In line with this, another member of the FoxO family, FoxO3, has been shown to transactivate the expression of the Lc3 gene in cardiomyocytes (56).…”
Section: -Immunized Rag1mentioning
confidence: 79%
See 1 more Smart Citation
“…Our findings provide evidence for a CTLA4-mediated transcriptional-dependent regulation of autophagy in DCs though activation of the PI3K/Akt axis that results in nuclear exclusion of FoxO1 and decreased transcription of Lc3b. Nuclear presence of FoxO1 is a prerequisite for transcriptional activation of autophagy genes in a process that is controlled by Akt (55). In line with this, another member of the FoxO family, FoxO3, has been shown to transactivate the expression of the Lc3 gene in cardiomyocytes (56).…”
Section: -Immunized Rag1mentioning
confidence: 79%
“…In line with this, another member of the FoxO family, FoxO3, has been shown to transactivate the expression of the Lc3 gene in cardiomyocytes (56). However, it was later delineated that FoxO3 upregulated the PI3K/Akt pathway, which phosphorylated FoxO1 and mediated FoxO1 shuttling from the nucleus (55). Interestingly, and in contrast with our results, earlier reports showed that CTLA4 binding induced FoxO3 nuclear localization in DCs (57, 58), but both studies did not provide a linear relationship between CTLA4 engagement and FoxO3 nuclear localization in DCs.…”
Section: -Immunized Rag1mentioning
confidence: 96%
“…It is expressed at low levels within breast cancer cells and exhibits the ability to affect the translation of forkhead box protein O1 (FOXO1) and FOXO3 (34,(38)(39)(40)(41). Additionally, evidence has revealed that FOXO1 regulates autophagy (42)(43)(44)(45)(46)(47)(48)(49). Primarily, the present study hypothesized that connections exist between miR-96 and autophagy, and that the likely target protein of this interaction is FOXO1.…”
Section: Introductionmentioning
confidence: 77%
“…FOXO transcription factors are known to regulate mitochondrial function (Ferber et al, 2012), cell metabolism (Hirota et al, 2008) and autophagy (Zhou et al, 2012;Zhao et al, 2007) in several cell types, but these effects of FOXO have not been clearly linked to VEGF signaling in the endothelium. Only recently, VEGF-mediated activation of cell surface receptors has been associated with suppression of FOXO1 (Zhuang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%